An innovative stand‐alone bioreactor for the highly reproducible transfer of cyclic mechanical stretch to stem cells cultured in a 3D scaffold. (3rd August 2012) - Govoni, Marco; Lotti, Fabrizio; Biagiotti, Luigi; Lannocca, Maurizio; Pasquinelli, Gianandrea; Valente, Sabrina; Muscari, Claudio; Bonafè, Francesca; Caldarera, Claudio M.; Guarnieri, Carlo; Cavalcanti, Silvio; Giordano, Emanuele
Abstract Much evidence in the literature demonstrates the effect of cyclic mechanical stretch in maintaining, or addressing, a muscle phenotype. Such results were obtained using several technical approaches, useful for the experimental collection of proofs of principle but probably unsuitable for application in clinical regenerative medicine. Here we aimed to design a reliable innovative bioreactor, acting as a stand‐alone cell culture incubator, easy to operate and effective in addressing mesenchymal stem cells (MSCs) seeded onto a 3D bioreabsorbable scaffold, towards a muscle phenotype via the transfer of a controlled and highly‐reproducible cyclic deformation. Electron microscopy, immunohistochemistry and biochemical analysis of the obtained pseudotissue constructs showed that cells 'trained' over 1 week: (a) displayed multilayer organization and invaded the 3D mesh of the scaffold; and (b) expressed typical markers of muscle cells. This effect was due only to physical stimulation of the cells, without the need of any other chemical or genetic manipulation. This device is thus proposed as a prototypal instrument to obtain pseudotissue constructs to test in cardiovascular regenerative medicine, using good manufacturing procedures. Copyright © 2012 John Wiley & Sons, Ltd.